GEJOLAK EMOSI REMAJA DALAM KARYA SENI LUKIS KONTEMPORER - Yasrul Sami, S.Sn., M.Sn., DANIEL HAPOSAN SIMBOLON, Drs. Ismanadi Uska, (Serupa The Journal of Art Education, 2016)
This final work aims to visualize the emotional turmoil of adolescence into the painting in a contemporary style. The author uses five stages in the creation of works of art, the preparation stage , the stage of elaboration , synthesis stage , the stage of realization of the concept , and the completion stage in the form of an exhibition of works end. The author uses acrylic paints in the creation of the work. The style that author use is contemporary. Contemporary art is not bound to rules that already exists. The ten works that author present made with headings, namely: 1) â€œJalan Pintasâ€, 2) â€œPenenangâ€, 3) â€œVirus Jalananâ€, 4) â€œLihat Kami!â€, 5) â€œDepresiâ€, 6) â€œDunia Merekaâ€, 7) â€œAntagonisâ€, 8) â€œBegal!â€, 9) â€œPenenang #2â€, 10) â€œGamesâ€.Kata Kunci : Gejolak Emosi Remaja, Seni Lukis, Kontemporer.